2020
DOI: 10.1186/s40360-020-0388-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective and therapeutic effects of nanoliposomal quercetin on acute liver injury in rats

Abstract: Background: Quercetin, a pigment (flavonoid) found in many plants and foods, has good effects on protecting liver function but poor solubility and bioavailability in vivo. A drug delivery system can improve the accumulation and bioavailability of quercetin in liver. In this study, we used liposomal nanoparticles to entrap quercetin and evaluated its protective and therapeutic effects on drug-induced liver injury in rats. Methods: The nanoliposomal quercetin was prepared by a thin film evaporation-high pressure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…The liver was weighed and the value recorded. The liver index (liver weight/body weight × 100%) was calculated ( Liu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The liver was weighed and the value recorded. The liver index (liver weight/body weight × 100%) was calculated ( Liu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 5 , an obvious elevation in white blood cell count (WBC) and lymphocyte count (LYM) could be observed in the model group compared with the control group (# p < 0.05), indicating abnormal regulation of autoimmunity and the development of inflammation. Furthermore, expression of the liver function indicators glutamic-oxaloacetic transaminase (GOT) and glutamic-pyruvic transaminase (GPT) were also increased markedly in the model group compared with the control group, as shown as Figure 6 (# p < 0.05), suggesting a decrease in liver function and the occurrence of parenchymal hepatic disease [ 25 , 26 , 27 ]. Through the above, it could be concluded that the liver injury model was successfully established.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the higher serum BUN in GINSENG might be linked with the ruminal NH 3 -N result. In a previous study, AST and ALT in serum were used as elements for the reliable hepatic diagnostics in animals [ 43 ]. The AST in the GINSENG was higher than that in CON (CON: 52.4 U/L; GINSENG: 70.0 U/L).…”
Section: Discussionmentioning
confidence: 99%